The Value for Money agenda: from a straitjacket to a learning approach. Issue 6 (18th August 2019) - D'Emidio, Francesca; Wallace, Tina
ABSTRACT: Value for Money (VfM) is increasingly a funding requirement for UK aid. This article builds on research around different VfM approaches to highlight the challenges faced by the sector in applying VfM for organisational evaluation and learning. It argues that the focus must be on: what is really changing for people, not only on how resources are used; involving communities in programmes and enabling them to play a key role in the VfM judgements; using VFM to inform future programme decisions; and ensuring these approaches become integral to organisational ways of working.